Rehabilitation Of Patient with Mandibular Denture Using Extracoronal Semiprecision Attachment Combined with Custom-Made Non-Rigid Connector – A Case Report - Sabita F X, Dr Maria Jenifer; Relan, Srishti; S G, Sushma; Chinmayi, Chinmayi; Kundu, Rohit; Kedar, Kedar (Journal of Neonatal Surgery, 2025)
The restoration of a partially edentulous arch can be a great challenge when there is a Kennedy’s class I or class II situation with unilateral or bilateral posterior teeth that are completely missing. It all the more becomes challenging in a long span fixed partial denture scenario where the forces would be substantial to the remaining abutment teeth. Successful restoration can be done with various conventional and contemporary treatment options. One such treatment modality is extracoronal semi-precision attachment retained cast partial dentures combined with a stress breaker for the long span fixed partial denture. This article describes a case report with mandibular Kennedy’s class 1 modification 2 partially edentulous arch rehabilitated with a cast partial denture having an extracoronal semi precision attachment (RHEIN 83 attachment system) and a customized non-rigid connector using pen refill.